Comparison of the effectivity of oral and intra-articular administration of tenoxicam in patients with knee osteoarthritis - Mesut Erbas; Tuncer Simsek; Hasan Ali Kiraz; Hasan Sahin; Huseyin Toman (Brazilian Journal of Anesthesiology, 2015)
Background and objectives: Tenoxicam is widely used in osteoarthritis treatment and we aimed to compare the effectivity of oral and intra-articular administration of tenoxicam in osteoarthritis treatment. Methods: This study was performed between 2011 and 2012 by retrospectively analyzing and comparing the findings of 60 patients who were clinically and radiologically diagnosed with knee degenerative osteoarthritis in Bünyan state hospital pain policlinic. 60 patients included in the study were divided into two groups. The first group (tenoxicam IA, n = 30) included patient findings of those subjected to intra-articular injection of 20 mg tenoxicam to the knee once a week for three weeks and the second group (oral tenoxicam, n = 30) included patients who were administered 20 mg oral tenoxicam once a day for three weeks. All patients were clinically evaluated pre-treatment and in the 1st week, 1st month and 3rd month post-treatment according to specified criteria. Results and conclusions: Twenty two of 60 patients included in the study were male and 38 were female. In both groups significant improvements were detected in all of the observed parameters: visual analog scale, Western Ontario McMaster Osteoarthritis Index (pain, physical activity, knee stiffness) and Lequesne index scores and in the evaluations performed in 1st week, 1st month and 3rd month with respect to pre-treatment values. Besides, a better compliance to treatment and gastrointestinal system tolerability in tenoxicam IA group was also observed. Intra-articular tenoxicam administration could be thought as an alternative treatment method in patients with knee osteoarthritis who cannot use oral tenoxicam especially due to systemic gastrointestinal system side effects and those who have difficulties in adapting to treatment. Resumo: Justificativa e objetivos: Tenoxicam é amplamente usado no tratamento da osteoartrite (OA) e o nosso objetivo foi comparar a eficácia de tenoxicam administrado por via oral (VO) e intra-articular (IA) no tratamento da OA. Métodos: Este estudo foi conduzido entre 2011 e 2012 por meio de análise retrospectiva e comparação dos resultados de 60 pacientes que foram clínica e radiologicamente diagnosticados com OA degenerativa de joelhos na Policlínica de Tratamento da Dor do Hospital Estadual de Bünyan. Os 60 pacientes incluídos no estudo foram alocados em dois grupos. O primeiro grupo (tenoxicam IA, n = 30) incluiu resultados de pacientes submetidos à injeção nos joelhos por via IA de 20 mg de tenoxicam uma vez por semana durante três semanas e o segundo grupo (tenoxicam VO, n = 30) incluiu pacientes que receberam 20 mg de tenoxicam por VO uma vez por dia durante três semanas. Todos os pacientes foram avaliados clinicamente na fase basal pré-tratamento e em uma semana, um mês e três meses pós-tratamento, de acordo com os critérios especificados. Resultados e conclusões: Dos 60 pacientes, 22 eram do sexo masculino e 38 do sexo feminino. Em ambos os grupos, melhorias significativas foram detectadas em todos os parâmetros da escala visual analógica, do índice Western Ontario and MacMaster (Womac – dor, atividade física e rigidez dos joelhos) e do índice de Lequesne nas avaliações feitas em uma semana, um mês e três meses e comparadas aos valores basais. Além disso, uma melhor adesão ao tratamento e tolerabilidade ao sistema gastrointestinal no grupo tenoxicam IA também foram observadas. A administração de tenoxicam IA pode ser considerada como um método opcional de tratamento em pacientes com OA de joelhos que não podem usar tenoxicam por VO, especialmente por causa dos efeitos colaterais sobre o sistema gastrintestinal, e naqueles com dificuldades de adaptação ao tratamento. Keywords: Osteoarthritis, Tenoxicam, Knee, Intra-articular administration, Palavras-chave: Osteoartrite, Tenoxicam, Joelhos, Administração intra-articular